Transforming Talent Management: The Journey to E-Human Resources Excellence - Tuli, Ferdouse Ara (Asian Business Review, 2023)
This study offers a comprehensive exploration of the dynamic evolution within human resources (HR) and the transformative journey of talent management in the digital era. Beginning with an examination of foundational talent management principles, the narrative traces the shift from traditional HR frameworks to the contemporary landscape of E-Human Resources (E-HR) excellence. The study emphasizes the role of digital technologies as catalysts for this evolution, showcasing their impact on optimizing recruitment, performance management, and employee engagement. Throughout, HR innovation emerges as a driving force, highlighting how novel approaches and technologies are reshaping the HR landscape. This initiative underscores the pursuit of excellence in talent management within the E-HR paradigm, outlining strategies and best practices for organizations to navigate and thrive in the complexities of the modern workforce. In essence, this exploration encapsulates the ongoing narrative of innovation and excellence in the transformative journey of talent management within the digital era, providing valuable insights for HR professionals, organizational leaders, and policymakers navigating the evolving HR landscape.